Factors Influencing the Incidence of Leptospirosis in the Work Area of the Tulakan Community Health Center, Pacitan Regency in 2025 - Agung Trianto; Arief Hargono; Ratih Dwi Arini (International Conference on Sustainable Health Promotion, 2025)
Introduction : Leptospirosis is zoonotic diseases caused by by bacteria Leptospira interrogation And transmitted from animal to man through contact direct with urine infected animals​ or polluted environment . Animals​ transmitter main is mice , although dogs , cows , and pigs can also become a reservoir . Research purposes​ this aim For analyze factor Gender and age risk factors influence the incidence of leptospirosis. in the working area of the Tulakan Community Health Center, Pacitan Regency in 2025. Method : Research observational analytic with a case control approach . Sample study This amounts to 84 people , for sample case totaling 42 people taken from all leptospirosis sufferers in January – August 2025 and for the control sample totaling 42 people with purposive sampling technique . Data collection using technique observation of secondary data, then data analysis in this study is analysis univariate (frequency distribution), bivariate analysis (chi square test). Results : Results study This show that There is no relationship between gender and the incidence of leptospirosis (p=0.274 ) and there is no relationship between age and the incidence of leptospirosis (p=0.867 ). Conclusion : There is no relationship between gender and age with the incidence of leptospirosis in the work area of the Tulakan Community Health Center, Pacitan Regency in 2025.